Pengaruh Campuran Terhadap Kuat Tekan Beton Agregat Recycle - Sulaiman, Lusman; Fisu, Amiruddin Akbar (Rekayasa Sipil, 2020)
High consumption of freshwater and natural aggregate in concrete production becomes a matter of some concern that has been discussed recent years. An alternative partially or totally replacement for both materials is significant issue to reduce the negative impacts on the environment. Therefore, the aim of this research is to observe explicitly the effect of using seawater as mixing combined with recycled coarse aggregate and other materials to make new recycled aggregate concrete (RAC) under compressive load. The experimental laboratory test was conducted to total of thirty cylinders specimens of two to groups of mix design with w/c of 0.45. First was three types of percentage level of recycled coarse aggregate with targeted compressive strength of 25 MPa. The second was two types of mixtures and totally replaced by recycled coarse aggregate with targeted compressive strength of 30 MPa. Some specimens were mixed by seawater and all were placed in the freshwater-curing during some definite period of 7 and 28 days. The results show that the seawater and recycle aggregate were not significant influence to reduce the compression strength for first mix category, while the second mix category was having great influence up to 22% at 28 day. The reduction in compressive strength increases with an increase the targeted compressive load.